(untitled) (Annals of the University of Bucharest. Philosophy Series, 2024)
As a philosopher or a lover of philosophy, one wonders whether this area can also be useful in everyday life; whether philosophy also has a reason that leads to happiness. Boethius tried to find the answer to this question in the 6th century through his writing Consolatio Philosophiae. The Lady Philosophy helps the prisoner Boethius see true goodness and choose authentic happiness. In this essay we try to analyze the text of the Consolatio Philosophiae and show how a happy life is possible through philosophy. We go through all the books and analyze the key passages of the Consolatio. At the same time, we follow the state of mind of Boethius and see how far he understands the prospect of happiness. From diagnosing Boethius (as established by Lady Philosophy) as banished in his existence, through understanding Fortuna as an ever-changing goddess, to true happiness, we accompany Boethius in his sorrows and doubts. The last questions of books four and five, the questions of the theodicy, refer to the justification of the philosopher to believe in a God who allows evil in the world and who supposedly does not predestine creation in his foreknowledge. The conclusions are partially redundant. It is up to the individual to decide whether philosophy can be a good companion on the way to eternal happiness. Some prerequisites of Boethian philosophy and theology could be established here.